"Discourses of discontent: fashion, feminism and the commodification of fat women's anger". Issue 3 (2nd September 2022) - Peters, Lauren Downing
ABSTRACT: This article considers the messy intersections of fat liberation and fashion. In doing so, it analyzes two case studies – Big Beautiful Woman magazine's "I'M MAD AS HELL!" complaint slips and the more recent "#MakeMySize" social media movement – through the critical lenses of commodity feminism and commodity activism. When viewed through these lenses, these case studies demonstrate that although some critics have deemed fashion a frivolous preoccupation, it has in fact played an important, if complicated, role in the ongoing project of resignifying fat embodiment and in pushing the fat liberation movement forward.